Hungarian Monitoring, 18 June 1988 . [Magyar rádiófigyelő], 1988. június 18 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - UN Security Council position in support of Pretoria convicted - Polish parliament after sitting Domestic Affairs: - Police organizations' statement on opposition mobilizations on the anniversary of Imre Nagy's death - Dangerous waste storage facility to be built in Nova - Great anticipation for summer Young Pioneers' camp - Lack of legislation protecting historical monuments Economy: - Finance minister on budget experiences to date Külpolitika: - Az ENSZ BT állásfoglalása a pretoriai elítéltek védelmében - A lengyel parlament ülése után Belpolitika: - A rendőri szervek nyilatkozata az ellenzéki megmozdulásról Nagy Imre halálának évfordulóján - A veszélyes hulladéktárolót Nován fogják felépíteni - Alig várható érdeklődés a nyári úttörőtábor iránt - Műemlékvédelmi jogszabály hiánya Gazdaság: - A pénzügyminiszter a költségvetés eddigi tapasztalatiról